Efficacy of Clinical Scoring in Diagnosing Malaria - Sherazi, Sajid Hussain; Khan, Zarmast; Zeb, Mian Rahmat; Basit, Muhammed; Ali, Izhar; Aleem Uddin, Muhammad (Journal of Neonatal Surgery, 2025)
Introduction: Malaria is one of the most widespread and deadly infectious diseases globally, primarily caused by Plasmodium parasites transmitted through the bites of infected female Anopheles mosquitoes. Objective: The main objective of the study is to find the efficacy of clinical scoring in diagnosing malaria in patients. Methodology: This prospective observational study was conducted at Niazi Medical and Dental College, Sargodha during June 2023 to July 2024. The study involved 185 patients presenting with symptoms of fever and other malaria-associated clinical features at the healthcare facility. Results: Data were collected from 185 patients, with a mean age of 32.4±3.71 years, ranging from 5 to 65 years. The majority of participants were adults aged 13–45 years (64.9%), while children (≤ 12 years) comprised 16.2%, and older adults (≥ 46 years) accounted for 18.9%. Of the total participants, 56.8% were male, and 43.2% were female. A significant portion had a travel history to malaria-endemic areas (45.9%), and 37.8% had a history of previous malaria. Common presenting symptoms included fever (100%), chills (75.7%), and headache (67.6%), while physical findings such as splenomegaly and hepatomegaly were observed in 21.6% and 13.5% of cases, respectively. Conclusion: It is concluded that the clinical scoring system is a highly effective tool for diagnosing malaria, demonstrating excellent sensitivity, specificity, and predictive values. It can serve as a reliable screening method, especially in resource-limited settings, where laboratory diagnostics may not always be readily available.